2006
DOI: 10.1245/aso.2006.03.089
|View full text |Cite
|
Sign up to set email alerts
|

Hemithyroidectomy: The Optimal Initial Surgical Approach for Individuals Undergoing Surgery for a Cytological Diagnosis of Follicular Neoplasm

Abstract: Overall, in the FN patient population, five hemithyroidectomies were performed to identify each cancer, and no further operation was required in 96% of patients. New diagnostic tools are needed to reduce the number of operations performed for benign pathology in patients with nodular thyroid disease and a needle biopsy diagnosis of FN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
1
25
2
Order By: Relevance
“…[8,[19][20][21] Male gender has also been found to be associated with malignancy in some studies, [19,22] while others found no difference between genders in terms of malignancy. [15,18,23] The results of multivariate analysis performed for this study demonstrated that suspicion of malignancy detected ultrasonographically was associated with risk of malignancy. Gharib et al [10] reported that sonographic characteristics of malignant thyroid nodules were irregular boundaries, the presence of calcification, hypoechogenicity, vascular abnormalities, and increased size.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[8,[19][20][21] Male gender has also been found to be associated with malignancy in some studies, [19,22] while others found no difference between genders in terms of malignancy. [15,18,23] The results of multivariate analysis performed for this study demonstrated that suspicion of malignancy detected ultrasonographically was associated with risk of malignancy. Gharib et al [10] reported that sonographic characteristics of malignant thyroid nodules were irregular boundaries, the presence of calcification, hypoechogenicity, vascular abnormalities, and increased size.…”
Section: Discussionmentioning
confidence: 66%
“…Other authors have also indicated the lack of any correlation between age and increase in the risk of malignancy. [15,17,18] However, in one study, patient age was demonstrated to be a marker for malignancy. [8,[19][20][21] Male gender has also been found to be associated with malignancy in some studies, [19,22] while others found no difference between genders in terms of malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…There are also currently no patient or tumor characteristics that can reliably predict the presence of cancer in individuals diagnosed with a thyroid neoplasm of Hurthle cell or follicular subtype. 3,4 Thus, when a thyroid tumor with this indeterminate cytology is identified by FNAB, the current recommended approach is a diagnostic operation for removal of either a portion of or the entire thyroid gland. [3][4][5] In addition to the emotional distress experienced by patients who undergo surgery for a possible cancer diagnosis, thyroid resection carries a low but significant risk of permanent injury to associated parathyroid glands and nerves that may lead to the need for life-long calcium supplementation or voice dysfunction, and extremely uncommonly the need for a long term tracheostomy.…”
mentioning
confidence: 99%
“…Indeed, only approximately one in five patients undergoing thyroid resection for indeterminant FNAB cytology will eventually be diagnosed with a thyroid cancer by histopathological evaluation. 3 Study of the molecular characteristics of thyroid cancer has allowed for the development of potential molecular diagnostic tools. In the largest thyroid cancer diagnostic marker panel study reported to date, we recently found Galectin-3 (Gal-3) to be the most accurate standalone marker for differentiated thyroid cancer diagnosis (DTC) when compared with a panel of 56 other molecular markers.…”
mentioning
confidence: 99%
“…Consistent with the current literature, in prior reports of our experience, only about 1 in 5 patients undergoing thyroid operation for FN or HN were eventually found by histopathologic evaluation to have cancer. 17,18 Hemithryoidectomy was considered to be adequate definitive treatment in 96% of individuals with FN and 82% with HN diagnosed preoperatively with FNAB cytology.…”
mentioning
confidence: 99%